Pemikiran Tasawuf K. H. Raden Abdullah Bin Nuh Dan Relevansinya Dalam Konteks Kehidupan Era Modern - Yasirul Musyaffa; M. Syukron Jazilah (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
K. H. Raden Abdullah Bin Nuh was a charismatic cleric who also acted as a scholar, writer, linguist, journalist, educator, radio broadcaster, and trilingual dictionary writer. He promoted the philosophy of lifelong education, which includes formal and informal learning in various locations and times. This study aims to examine the concept of Sufism of K. H. Raden Abdullah Bin Nuh and its relevance in modern life. This study uses a Library Research approach to collect data from relevant books, journals and scientific articles. The analysis of K. H. Raden Abdullah Bin Nuh's Sufism thoughts was carried out using a philosophical method to understand the concept of Sufism as a whole and relate it to a broader context. This study found that K. H. Raden Abdullah bin Nuh taught Sufism by referring to the examples of the Prophet, his companions, and scholars such as Imam Syafi'i and Al-Ghazali. The Sufism he developed, along with Sufi Islamic psychology, aimed to help humanity face the challenges of life, and achieve balance between worldly life and the hereafter. Through dhikr, worship, and example based on the Koran and Sunnah, he teaches Sufism as a way to heal and protect individuals from various problems.